Pengaruh Indeks Pembangunan Manusia, Pendapatan Perkapita Dan Pertumbuhan Ekonomi Terhadap Kemiskinan Di Kabupaten Hulu Sungai Selatan Tahun 2005-2019 - Sinta Sinta; Eny Fahrati (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to determine the effect of the human development index, per capita income, and economic growth on poverty in the Hulu Sungai Selatan regency from 2005-to 2019.            This research is included in quantitative research, and the method used is multiple linear regression using time series secondary data processed with the help of the SPSS-26.0 program.            The results of this study (1) The variables of Human Development Index, Per capita Income, and Economic Growth have a simultaneous effect on poverty in Hulu Sungai Selatan Regency. (1) The most dominant factor is the Per capita Income variable. To accelerate the decline in the poverty rate, it is necessary to increase economic activity in all sectors, especially potential sectors such as agriculture, mining, trade, and government, and improve the quality of knowledge and skills so that the amount of Gross Regional Domestic Product generated can support people's income.